2021
DOI: 10.3390/horticulturae7110432
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Hydroponic Cropping System on Growth, Yield, and Nutrition of a Greek Sweet Onion (Allium cepa L.) Landrace

Abstract: Nerokremmydo of Zakynthos, a Greek landrace of sweet onion producing a large bulb, was experimentally cultivated in a glasshouse using aeroponic, floating, nutrient film technique, and aggregate systems, i.e., AER, FL, NFT, and AG, respectively. The aim of the experiment was to compare the effects of these soilless culture systems (SCSs) on plant characteristics, including fresh and dry weight, bulb geometry, water use efficiency, tissue macronutrient concentrations, and uptake concentrations (UC), i.e., uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Nutrients are directly taken up by plants and stimulate the composition of different phytochemicals, such as ascorbic acid, phenolic compounds and flavonoids in plants [ 10 , 26 ]. The plant takes up nutrients through its roots with little effort and makes full use of its energy to grow tissues as compared to the soil system [ 27 , 28 ]. In contrast, plants growing in soil and substrate cultivation systems benefit from soil nutrient mineralization and microbial activity [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients are directly taken up by plants and stimulate the composition of different phytochemicals, such as ascorbic acid, phenolic compounds and flavonoids in plants [ 10 , 26 ]. The plant takes up nutrients through its roots with little effort and makes full use of its energy to grow tissues as compared to the soil system [ 27 , 28 ]. In contrast, plants growing in soil and substrate cultivation systems benefit from soil nutrient mineralization and microbial activity [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…The harvesting period is 2–4 days for rice grass, 6–9 days for barley grass, 6–9 days for wheat grass, 6–9 days for oat grass, 8–12 days for jowar grass, 7 days for maize grass, 7–14 days for buckwheat, 4–6 days for mung bean, 6–8 days for chickpea, 12–14 days for mint, 20 days for basil, 18–20 days for sage, 16–22 days for oregano, 9–12 days for amaranth, 10–12 days for beet, 8–12 days for chard, 12–21 days for red swiss chard, 10–17 days for quinoa, 4–6 days for spinach, 14–25 days for chives, 12–14 days for garlic, 10–12 days for leeks, 12 days for onion, 15–25 days for carrot, 7–21 days for dill, 21–30 days for celery, 10–14 days for fennel, 5–10 days for radish, 5–20 days for aster cress, 8–16 days for mustard, 7–12 days for sunflower, 7–21 days for linseed, 7–21 days for cucumber, 4–20 days for Jute, 7–21 days for squash, 7–14 days for chicory, 8–16 days for endive, 7–16 days for lettuce, 7–21 days for beans, 7–28 days for welsh onion, 9–21 days for long green onion, 7–16 days for coriander, and 6–14 days for fenugreek ( Table ) .…”
Section: Factors Affecting In Microgreen Plant Production In Soilless...mentioning
confidence: 99%
“…Among these publications, three studied the effects of fertilizers, including organic and macro-and micro-nutrient fertilizers, on the growth and nutrient uptake of vegetables [1][2][3]. Two articles described the effects of water and nutrient supply using irrigation or hydroponic supplying systems on the yield and quality of vegetables [4,5]. Four articles investigated the effects of environmental conditions (mainly light and temperature) on the growth and quality of vegetables [6][7][8][9].…”
Section: Special Issue Overviewmentioning
confidence: 99%
“…The ratio of water and nutrients determines the strength of the nutrient supply, which is also a key factor in the yield forming and quality optimization of horticultural crops. Mouroutoglou et al [5] compared the effects of four soil-less culture systems (i.e., aeroponic, floating, nutrient film technique, and aggregate systems) on growth, yield, and nutrient uptake in the Greek sweet onion landrace. The results showed that the highest plant biomass, onion yield, and water use efficiency were obtained in floating and aggregate systems, mainly due to the sufficient water and nutrient supply and decreased limit on root growth, when compared with the nutrient film technique.…”
Section: Water and Nutrient Supplymentioning
confidence: 99%